Losartan (DUR-753) blocks the natriuretic, kaliuretic and antidiuretic effect of intracerebroventricular injection of carbachol in water-loaded rats - Saad, William A. [UNESP]; Luiz, A. C. [UNESP]; Camargo, L. A.A. [UNESP]; Renzi, A. [UNESP]; Menani, J. V. [UNESP] (My University, 1996)
We determined the effect of intracerebroventricular (icv) administration of losartan, an angiotensin II (ANG II) subtype 1 receptor (AT1) antagonist, on icv carbachol-induced natriuresis, kaliuresis and antidiuresis in water-loaded male Holtzman rats (250-300 g) with a cannula implanted into the lateral ventricle (LV). The rats were water loaded with 5% of their body weight by gavage twice, with the second gavage one hour after the first. Carbachol (2 nmol in 1 μl) was injected icv immediately after the second load. When losartan (DUP-753, 50 nmol in 1 μl) was administered icv, it was given 3 min before carbachol. Previous icv treatment with losartan significantly reduced the icv carbachol-induced natriuresis (324 ± 17 μEq/120 min), kaliuresis (103 ± 15 μEq/120min) and antidiuresis (13.5 ± 2.1 ml/120 min) compared to the effects of previous icv injection of saline (Na+ excretion = 498 ± 22 μEq/120 min; K+ excretion = 167 ± 20 μEq/120 min; urine volume = 5.2 ± 1.2 ml/120 min). These results, reported as means ± SEM for 12 rats in each group, are consistent with the hypothesis that AT1 subtype receptors participate in the regulation of body electrolyte balance.
Keywords: Angiotensin II; AT1 receptors; Carbachol; DUP-753; Electrolyte balance; Losartan